ANALISIS KESULITAN SISWA DALAM MENANGANI PERMASALAHAN MATEMATIKA TERBUKA (MATHEMATIC OPEN-ENDED PROBLEMS) - Payadnya, I Putu Ade Andre; Jayantika, I Gusti Agung Ngurah Trisna (Jurnal Santiaji Pendidikan (JSP), 2018)
This research aimed at: 1) analyzing the students’ difficulty on solving mathematic open-ended problems, 2) analyzing the implementation of conducted mathematic’s learning. Subjects of the study was the whole grade VIII A8 students in SMP Negeri 1 Singaraja with the total number was 28 students. The data collection methods used in this research were observation, test, and interview. The technique of data analysis in this study made use qualitative descriptive analysis that was to analyze and describe every problem and difficulty that students faced when solving mathematic open-ended problems. The results from the test, interview, and observation analysis showed that the students’ difficulty on solving mathematic open-ended problems are:1) the students’ lack of ability on understanding mathematic open-ended problems, 2)the students had poor reasoning ability in which the students usually is a non-effective reasoning, 3) the stdudents’lack of representation ability and real thinking ability on solving the problems so that the students cannot find the best method to solve the problems. The researcher’s advise is that the mathematic teachers have to point on conceptual understanding and thinking ability development when teaching mathematics subject on classes.